CHARACTERISTICS OF ZINC-BINDING TO HUMAN RED-BLOOD-CELL MEMBRANES - Brandaoneto, J.; Bell, W. R. (Wiley-Blackwell, 1994)
The objective of the present study was to standardize the analysis of zinc binding on human red blood cell (RBC) membranes in 20 normal adults. The displacement studies revealed that at the maximal stable zinc concentration tested (600 muM), 57% (mean) of the bound Zn-65 was displaced and to displace half maximal Zn-65, the stable zinc concentration was 300 muM. Scatchard plots revealed two classes of binding sites for zinc on RBC membranes: one with higher affinity, Kd = 1.20 x 10(-5) M (site I), and the other with lower affinity, Kd = 2.77 x 10(-4) M (site II). Binding sites occupancy was 97% means and 58.5% means for sites I and 11, respectively. The displacement was affected by temperature, membrane protein concentration, freezing, thawing, and dialysis. Other metal cations, including Co++, Fe++, and Mn++, had very little effect on Zn-65 displacement, in contrast copper displaced Zn-65 from its binding sites on RBC membranes. Zinc binding to RBC membranes was rapid and readily reversible in a dynamic equilibrium with its binding sites. It is anticipated that this method will be applicable to studies of a wide variety of diseases specifically related to zinc metabolism in humans as well as in animals. (C) 1994 Wiley-Liss, Inc.
Keywords: ERYTHROCYTE GHOST; ZINC BINDING SITES; TRACE ELEMENTS; NORMAL INDIVIDUALS